Implementasi Sikap Toleransi Beragama dan Pengaruhnya Bagi Anak di Era Disrupsi - Parida, Naumi; Kurniawati, Yuni; Willyam, Verry (STIPAK Malang, 2023)
Abstract: The purpose of research in this journal is that the implementation of religious tolerance can affect children's thinking patterns in understanding and appreciating the diversity of religions around them. The research method used in this paper is a literature method where the source material is obtained based on references from books, journals, articles related to the theme discussed. In this study there were several serious religious conflicts and intolerance among Indonesian society, resulting in rejection of the construction of places of worship, blasphemy, and persecution of certain religious groups. Based on the results of each existing study, it is concluded that Indonesia needs an understanding of tolerance in differences, especially religion. Tolerance in diversity is very important for every society to have and must be instilled from an early age in individual Indonesian society. With the attitude of religious tolerance in children, it will prepare children as the next generation of the nation to have an attitude of mutual respect, respect for differences, and live the freedom of rights in choosing each other's beliefs.Abstrak: Tujuan penelitian dalam jurnal ini adalah agar implementasi sikap toleransi beragama dapat memengaruhi pola berpikir anak dalam memahami dan menghargai keragaman agama di sekitarnya. Metode penelitian yang dipakai dalam tulisan ini ialah metode kepustakaan yang dimana sumber materi didapatkan berdasarkan referensi dari buku-buku, jurnal, artikel yang terkait dengan tema yang dibahas. Dalam penelitian ini terjadi beberapa konflik agama dan intoleran secara serius di kalangan masyarakat Indonesia, sehingga terjadilah penolakan pembangunan tempat ibadah, penistaan agama, dan penganiayaan terhadap kelompok agama tertentu. Berlandaskan hasil setiap kajian yang ada, maka disimpulkan bahwa Indonesia memerlukan pemahaman sikap toleransi dalam perbedaan terutama agama. Sikap toleransi dalam keberagaman sangatlah penting untuk dimiliki oleh setiap masyarakat dan harus ditanamkan sejak dini dalam diri individu masyarakat Indonesia. Dengan adanya sikap toleransi beragama dalam diri anak maka akan mempersiapkan anak sebagai generasi penerus bangsa untuk memiliki sikap saling menghargai, menghormati perbedaan, dan menghidupi kebebasan hak dalam memilih keyakinan satu sama lain.